Potential Regeneration of Mangrove Coastal of Payum Beach Merauke District - Stenly M.B.S Wairara; Reny Sianturi (Faculty of Agriculture Musamus University, 2019)
The purpose of this study was to analyze the regeneration potential of mangroves found on the coast of Payum, Merauke Regency, Papua Province. This research was conducted in August-October 2018. The data collection technique was purposive sampling using Transect Line Plots. The sampling location was chosen based on the representation of the presence of mangroves in three locations, namely zones A, B and C. The results of this study explained that there were three tree-level mangrove species, namely Avicennia alba, Rhizophora apiculata and Sonneratia alba. Type A. alba dominates in zone A with an important value index (INP) of 205.76%, zone B does not have a certain type that dominates, while Rhizophora apiculata dominates in zone C with INP 185.35%. The potential of the three mangrove species in zones A, B and C is good. Aegialitis annulata species are only found in sapling and seedling levels. In zones A and B are classified as new while in zone C is classified as bad. This study concluded that Avicennia alba, Rhizophora apiculata and Sonneratia alba had the potential to regenerate in all three locations (Zones A, B and C) compared to Aegialitis annulata.